Molecular Characterization of Fungi Associated with Pod Rot of the African Locust Beans (Parkia biglobosa) - Lateef A. A; Naher L; Abdulkareem M. A.; Ajijolakewu K. A; AbdulMalik A. O.; AbdulMalik A. O. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Parkia biglobosa is the African locust bean, native to West Africa and majorly used in the production of “Iru”, a local soup sweetener in various African delicacies as alternative to monosodium glutamate (MSG) which has detrimental long-term effects in the body. However, pod rot disease of the P. biglobosa pods leads to considerable losses in “Iru” production. This study was therefore carried out to identify the causal pathogen associated with Parkia biglobosa pod rot disease using sanger sequencing. Twelve diseased pods of P. biglobosa were collected and processed for isolation of the fungal pathogen based on their morphological characteristics. Genomic DNA was extracted from the isolate, amplified with primers ITS5/ITS4 and Sanger sequencing of the internal transcribed spacer (ITS) region of the pathogen was used to identify the fungal pathogen with the molecular analysis software Molecular Evolutionary Genetics Analysis (MEGA). Pathogenicity test was carried out to confirm the potential of the isolated pathogen to cause the implied disease. The pathogen was identified as Pseudofusicoccum violaceum with 562 bp and 99-100 % sequence identity with GenBank database. Koch’s postulates confirmed the pathogenicity of the isolate on P. biglobosa pods. This study constitutes the first report of Pseudofusicoccum violaceum as the causal pathogen of P. biglobosa pod rot in Nigeria. The findings from this study provide information on the ecological significance of Pseudofusicoccum violaceum as pathogen on P. biglobosa and possible control strategies of the disease caused.